The Effect of Lycopene Addition on the Semen Quality of Saanen Goats Stored at 5°C for 24 hours - Sigit Bintara; Diah Tri Widayati; Widya Asmarawati; Riyan Nugroho Aji (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2023)
In order to increase the livestock population, a good reproductive process was needed. Lycopene which belongs to carotenoid group has a dark yellow pigment. This study aimed to determine the effect of adding lycopene on the semen quality of Saanen goats. The research design used 4 treatments, P0 (egg yolk tris diluent) as control), P1 (egg yolk tris diluent + 2% lycopene), P2 (egg yolk tris diluent + 4% lycopene), and P3 (yolk tris diluent). egg + 6% lycopene). The quality of semen was observed after 24 hours of storage at 5℃. Macroscopic data were analyzed descreptively and the microscopic one was analyzed using a completely randomized design (CRD). The results showed that the addition of lycopene in egg yolk tris diluent had a significant (P<0.05) effect on the semen quality of Saanen goats. The results showed that the motility of spermatozoa in each treatment group (P0, P1, P2, and P3) was 60.1 ± 5.7%, 65.2 ± 4.3%, 62.4 ± 5.2%, and 60.6 ± 4.7%, respectively, viability were 65.3 ± 4.8, 73.5 ± 4.2, 70.4 ± 3.8, and 66.1 ± 5.1, respectively, abnormality were 17 ± 1.8%, 16 ± 1.8%, 18 ± 1.9%, and 16 ± 1.7%, respectively, and membrane integrity were 63 ± 3.3%, 70 ± 3.6 %, 67 ± 3.2%, and 62 ± 2.9%, respectively. Based on the results, it could be concluded that the lycopene addition improved the semen quality of Saanen goats compared to controls.